A new genus of Phlugidini (Orthoptera: Tettigoniidae: Meconematinae) with asymmetrical mandibles - Chamorro-Rengifo, Juliana; Olivier, Renan Da Silva (Zootaxa, 2017)
During collection of katydids carried out in the state of Mato Grosso do Sul, Brazil, five individuals of a species belonging to Phlugidini were captured. Males have remarkable asymmetric mandibles, different from those of the already known genera. The female is very similar to one recently described from Bolivia in genus Phlugiola Karny, 1907. However, male and female feature a combination of characters that does not conform to that genus. Here we propose a new monospecific genus, Anisophlugis Chamorro-Rengifo & Olivier n. gen., whose type species is Phlugiola appendicula Gorochov, 2015.